2021
DOI: 10.3390/biom11121843
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epithelium-Derived Cytokines in Atopic Dermatitis and Psoriasis: Evidence and Therapeutic Perspectives

Abstract: Atopic dermatitis and psoriasis are two of the most common chronic skin conditions. Current target therapies represent viable and safe solutions for the most severe cases of these two dermatoses but, presently, several limitations exist in terms of efficacy and side effects. A new class of products, epithelium-derived cytokines (TSLP, IL-25, IL-33), show an increasing potential for use in target therapy for these patients, and demonstrate a direct link between a generalized inflammatory and oxidative stress st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 80 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Cytokines have been proven to possess pro-inflammation and immunodepression actions. Cytokines have developed promptly, leading to the induction of dermatitis ( 29 ). Previous evidence has suggested that As impacts the production of inflammatory cytokines in the skin, causing allergic dermatitis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines have been proven to possess pro-inflammation and immunodepression actions. Cytokines have developed promptly, leading to the induction of dermatitis ( 29 ). Previous evidence has suggested that As impacts the production of inflammatory cytokines in the skin, causing allergic dermatitis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epithelial cell-derived TSLP has attracted much attention as cytokines that induce allergic immune responses. 32 TSLP is released by primary epithelial cells in response to certain microbial products, physical injury, or inflammatory cytokines. 33 Although the results of this study did not show a trend toward higher TSLP levels in patients with higher BSA indicated by the red dots in Figure 1D, it may be that TSLP is more likely to be produced by epidermal keratinocytes in patients with EB who often have chronic wounds prone to infection and cutaneous dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…TSLP is an epithelial cell‐derived immunostimulatory factor that activates immune cells such as dendritic cells, T cells, and mast cells. Recently, epithelial cell‐derived TSLP has attracted much attention as cytokines that induce allergic immune responses 32 . TSLP is released by primary epithelial cells in response to certain microbial products, physical injury, or inflammatory cytokines 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, recently this scenario was further complicated by the discovery of new cytokines involved in Th2 immunity, as epithelium-derived cytokines, namely, Interleukin 25 (IL-25), interleukin 33 (IL-33) and Thymic Stromal Lymphopoietin (TSLP), which have demonstrated to trigger Th2 immunity in response to external stimuli on skin [ 24 , 25 ]. Anyway, the relationship between these new mediators of Th2 response and adipokines has not been fully understood.…”
Section: Obesitymentioning
confidence: 99%